EDUKASI GAYA HIDUP HIPERTENSI DAN PENGUKURAN TEKANAN DARAH SEBAGAI UPAYA MANAJEMEN DIRI - Anggita, Kheniva Diah; Yoselina, Prima; Marni, Linda; Armaita, Armaita (Ensiklopedia of Journal, 2025)
Abstract: The importance of routine health checks is an important preventive step in early detection of health problems and maintaining the quality of life of the community. Hypertension is still a public health problem including in Ampalu. An unhealthy lifestyle is a dominant factor in the triggering of hypertension. Therefore, this community service is carried out with the aim of educating the community about a healthy lifestyle and regular blood pressure checks to avoid hypertension. The method used in community service has three stages, namely the stage of finding priority problems and deciding on solutions to problems. The second stage with intervention and the final stage with evaluation of the intervention. It is hoped that residents will understand and know more about hypertension from its definition to its prevention. A healthy lifestyle needs to be encouraged and promoted through various means, so that the community can avoid hypertension. Keywords: Hypertension, Education, Lifestyle, and Self-Management